Cerebellar Ataxia With Anti-DNER Antibodies: Outcomes and Immunologic Features. Issue 5 (8th September 2022) - Peter, Elise; Do, Le Duy; Hannoun, Salem; Muñiz-Castrillo, Sergio; Vogrig, Alberto; Wucher, Valentin; Pinto, Anne-Laurie; Chounlamountri, Naura; Zakaria, Walaa; Rogemond, Veronique; Picard, Geraldine; Hedou, Julien-Jacques; et al.
Abstract : Background and Objectives: There is no report on the long-term outcomes of ataxia with antibodies against Delta and Notch-like epidermal growth factor–related (DNER). We aimed to describe the clinical-immunologic features and long-term outcomes of patients with anti-DNER antibodies. Methods: Patients tested positive for anti-DNER antibodies between 2000 and 2020 were identified retrospectively. In those with available samples, immunoglobulin G (IgG) subclass analysis, longitudinal cerebellum volumetry, human leukocyte antigen isotyping, and CSF proteomic analysis were performed. Rodent brain membrane fractionation and organotypic cerebellar slices were used to study DNER cell-surface expression and human IgG binding to the Purkinje cell surface. Results: Twenty-eight patients were included (median age, 52 years, range 19–81): 23 of 28 (82.1%) were male and 23 of 28 (82.1%) had a hematologic malignancy. Most patients (27/28, 96.4%) had cerebellar ataxia; 16 of 28 (57.1%) had noncerebellar symptoms (cognitive impairment, neuropathy, and/or seizures), and 27 of 28 (96.4%) became moderately to severely disabled. Half of the patients (50%) improved, and 32.1% (9/28) had no or slight disability at the last visit (median, 26 months; range, 3–238). Good outcome significantly associated with younger age, milder clinical presentations, and less decrease of cerebellar gray matter volumes at follow-up. No human leukocyte antigen association was identified. Inflammation-related proteins were overexpressed in the patients' CSF. In the rodent brain, DNER was enriched in plasma membrane fractions. Patients' anti-DNER antibodies were predominantly IgG1/3 and bound live Purkinje cells in vitro. Discussion: DNER ataxia is a treatable condition in which nearly a third of patients have a favorable outcome. DNER antibodies bind to the surface of Purkinje cells and are therefore potentially pathogenic, supporting the use of B-cell–targeting treatments.